Value and Valorisation of Space: Notes for a Debate on Critical Geography - Costa, Bruno Moreira Riani [UNESP] (Wiley, 2024)
This article delves into the concept of valorisation of space, a prominent notion in Marxist geographical literature in Brazil. We critically examine this concept—stemming from a theoretical approach introduced in the 1980s during the critical renewal of Brazilian geography—by juxtaposing it with contributions from the Marxist value-form tradition. This comparison reveals certain operational limits in the concept of valorisation of space. Nevertheless, these limitations can be overcome by more precisely defining it as a subset of practices within the broader context of space production: it can be conceptualised as a specific type of space production, occurring when space itself becomes the subject of valorisation. Furthermore, we explore the potentialities of the concept, showcasing its operationalisation through concrete examples of dynamics within the Brazilian territory.
Keywords: critical geography; production of space; valorisation of space; value; value-form